2023
DOI: 10.1111/jon.13111
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cerebral autoregulation in Fabry disease: A case‐control study

Abstract: Background and Purpose Cerebral small vessel disease is a common manifestation among patients with Fabry disease (FD). As a biomarker of cerebral small vessel disease, the prevalence of impaired cerebral autoregulation as assessed by transcranial Doppler (TCD) ultrasonography was evaluated in FD patients and healthy controls. Methods TCD was performed to assess pulsatility index (PI) and vasomotor reactivity expressed by breath‐holding index (BHI) for the middle cerebral arteries of included FD patients and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“… 51 , 52 , 53 , 58 , 63 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 75 , 77 , 78 , 80 , 81 , 83 , 86 , 87 , 91 The remaining 18 studies were prospective or retrospective cohort studies. 54 , 55 , 56 , 57 , 59 , 62 , 72 , 73 , 74 , 76 , 79 , 82 , 84 , 85 , 92 , 93 , 94 , 95 In 203 patients with leukoaraiosis, Bian et al 91 demonstrated that patients exhibiting more severe white matter hyperintensities (Fazekas grades II and III) had a significantly reduced cerebrovascular reactivity compared with those with lower severity. In another larger cohort study, Staszewski et al 58 reported that in 120 subjects, the lowest tertile of cerebrovascular reactivity had a 19‐fold greater likelihood of having cSVD compared with the highest tertile.…”
Section: Resultsmentioning
confidence: 99%
“… 51 , 52 , 53 , 58 , 63 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 75 , 77 , 78 , 80 , 81 , 83 , 86 , 87 , 91 The remaining 18 studies were prospective or retrospective cohort studies. 54 , 55 , 56 , 57 , 59 , 62 , 72 , 73 , 74 , 76 , 79 , 82 , 84 , 85 , 92 , 93 , 94 , 95 In 203 patients with leukoaraiosis, Bian et al 91 demonstrated that patients exhibiting more severe white matter hyperintensities (Fazekas grades II and III) had a significantly reduced cerebrovascular reactivity compared with those with lower severity. In another larger cohort study, Staszewski et al 58 reported that in 120 subjects, the lowest tertile of cerebrovascular reactivity had a 19‐fold greater likelihood of having cSVD compared with the highest tertile.…”
Section: Resultsmentioning
confidence: 99%